The clamp rod internal fixator application and results in 120 small animal fracture patients - Zahn, K.; Matis, U. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
The clamp rod internal fixator (CRIF), also known as VetFix, consists of clamps that are slid onto a rod and fixed to the bone with screws. The objective of the present study was to evaluate the results of using the CRIF in 50 canine and 70 feline patients with closed (n = 93) and open (n = 10) transverse, oblique and comminuted fractures of the femur, tibia, humerus, acetabulum, radius, scapula and ulna. Fourteen further fractures were non-unions. In addition, the CRIF was used to repair three fracture-luxations of the spine. Fracture fixation was performed by application of one or two CRIF devices with 2.0, 2.7 or 3.5 mm cortical screws, using AO osteosynthesis instrumentation. Forty-five dogs and 55 cats were re-evaluated clinically and radiographically after an average of five months. Uneventful fracture healing occurred in 75 of these patients. In ten cases, follow-up was only available until six weeks post-surgery at which time fracture healing was incomplete. Of the total of 15 complications, five were resolved by exercise restriction alone, while the CRIF had to be replaced in six other patients. One cat with a spinal fracture-luxation was euthanized due to deterioration of neurological status. Three animals were unavailable for further follow-up. With the inclusion of both uneventful and complicated fracture healing, 86/90 patients ultimately achieved complete fracture healing. Our results suggest that the CRIF system can be used successfully to treat a great variety of fractures in dogs and cats.
Keywords: Dog; cat; fracture repair; VetFix; Internal Fixator